The Use of Smart Devices for the Detection of Aflatoxin in Ground Corn Feeds - Santos, Gil Nonato C. (Animo Repository, 2018)
Aflatoxins are toxic and carcinogenic secondary metabolites produced predominantly by two fungal species: Aspergillus flavus and Aspergillus parasiticus (Gourama, H., & Bullerman, L., 1995). These fungal species are contaminants of food crops as well as animal feeds, and are responsible for aflatoxin contamination of these agricultural products. The toxicity and potency of aflatoxins make them the primary health hazard as well as responsible for losses associated with contaminations of processed foods and feeds (Gourama, H., & Bullerman, L., 1995). Determination of aflatoxins concentration in food crops and animal feeds is thus very important for Food Safety Regulatory Agencies (FRSA) to create effective policies (Shane, S.H. & Groopman, J.D., 1994). However, the current mechanism of aflatoxin detection does not provide an immediate result, requires technical expertise, and are costly (Paniel, N., Radoi, A. & Marty, J., 2010)